Organizações matemáticas para o ensino de medida de área de triângulos: o trabalho da técnica - Fonda, Caroline Rodrigues da Silva (2020)
This study aims to present a proposal of didactic praxeologies for teaching area of triangles, using the Anthropological Theory of Didactics as a theoretical framework. For the constitution of our research corpus, a survey of the área of triangles by history, from the time of the Egyptians, was carried out, in order to detect mathematical praxeologies whose task was to "calculate the measure of the area of triangles". In search of answers to the following research question: “Is it possible to build didactic organizations that allow working with different techniques for teaching the calculation of the measure of the area of triangles in the final years of elementary school and in high school?”, We examined official documents and textbooks to identify how the area of triangles is placed in our basic education. As a result, we point out the lack of diversity in teaching methods to obtain the measurement of the area of triangles, in addition to an approach that favors the learning of the area as a greatness